AUTOMATED CUTTING TOOLS SELECTION FOR BEARINGS COMPONENTS TURNING PROCESS - DAN GEORGE PRUTICA; GHEORGHE BRABIE; BOGDAN CHIRITA (Journal of Engineering Studies and Research)
Due to the high potential of improving efficiency and productivity in machining operations, the automated cutting tools selection and the optimization of cutting parameters has been an area of high interest for many researchers in the frame of CAPP systems development. Through the work presented in this paper an automated cutting tools selection algorithm for roughing and finishing turning has been realized. An example for turning of the outer rings for large-size single row cylindrical roller bearings has been presented to illustrate the application of the proposed algorithm and analyze the results.